Five-Year Plan for 1961-62 Government of Bihar - Planning Commission (Planning Commission, 1961)
Jails, Scientific Departments, Education, Medical, Public Health, Agriculture, Animal Husbandry, Co-operation, Industries and Supplies, Labour and Employment, Community Development Projects, Civil Works.
Finance Department, Government of Bihar